2009
DOI: 10.1002/em.20445
|View full text |Cite
|
Sign up to set email alerts
|

In vitro genotoxic assessment of xenobiotic diacylglycerols in an in vitro micronucleus assay

Abstract: Xenobiotic diacylglycerols (DG) may induce pathological disorders by causing abnormal chromosomal segregation, which could be aneuploid. In this study, seven xenobiotic-diacylglycerols (four of drug origin and three of pesticide origin) were evaluated for their ability to induce aneuploidy in mammalian cultures using in vitro cytokinesis blocked micronucleus (CBMN) assay coupled with kinetochore labeling and interphase fluorescent in situ hybridization. Out of seven xeno-DGs, two (ibuprofen-DG and fenbufen-DG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
(39 reference statements)
1
5
0
1
Order By: Relevance
“…As it was detected in the present study, pesticide treatment may lead to significant increase in loss of heterozigosity. The effects of pesticide treatment on ploidy (threefold to 10‐fold increase in chromosome losses) have been reported by other authors (; Raimondi et al, ; Kayani et al, ). Study of Raimondi et al () reports 10‐fold increase in the loss of the chromosome 9 after exposure of human peripheral blood lymphocytes to benomyl, a benzimidazole derivative.…”
Section: Discussionsupporting
confidence: 74%
“…As it was detected in the present study, pesticide treatment may lead to significant increase in loss of heterozigosity. The effects of pesticide treatment on ploidy (threefold to 10‐fold increase in chromosome losses) have been reported by other authors (; Raimondi et al, ; Kayani et al, ). Study of Raimondi et al () reports 10‐fold increase in the loss of the chromosome 9 after exposure of human peripheral blood lymphocytes to benomyl, a benzimidazole derivative.…”
Section: Discussionsupporting
confidence: 74%
“…As Parolini et al ( 2011 ) suggested, living organisms are able to transform parent compound into more toxic intermediates. Such situation was observed by Kayani et al ( 2009 ) for ibuprofen conjugated with diacylglycerol (ibuprofen-DG), where conjugate was responsible for inhibition of cell division and nondisjunction in several pairs of chromosomes. Parolini et al ( 2011 ) demonstrated that chronic exposure to the environmentally relevant concentrations of ibuprofen (0.2, 2.0, and 8.0 μg/L) induced moderate genetic and cellular damage in zebra mussel, Dreissena polymorpha , a reference biological model sensitive to various pharmaceuticals, including antibiotics.…”
Section: Monocyclic Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 65%
“…Furthermore, all additional consequences like changes in growth rate, behavior, reproduction and alterations at biochemical level are observed. Kayani et al (2009) observed that conjugation of Ibuprofen and diacylglycerol (ibuprofen-DG) was accountable for the inhibition of cell division and non-disjunction of chromosomes to several pairs. Han et al ( 2010) investigated the chronic toxicity of ibuprofen by hormonal balance under in vitro condition using the H295R cell line on Oryzias latips, Moina macrocopa and Daphenia magna.…”
Section: Source Occurrence and Toxicity Of Ibuprofenmentioning
confidence: 99%